Sunitinib toxicity management – a practical approach - Sehdev, Sandeep (Canadian Urological Association Journal, 2016)
This article summarizes the adverse events (AEs) of sunitinib that are commonly encountered in a community oncology practice, and provides practical recommendations for their management based on the available literature and on the author’s own experience.